A Study Analysis And Survey of Different Performance Testing Tools Used For Cloud Applications - Pandit, Anuj; Shaha, Pritam; Bhambure, Sanket; Manjula, R (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing has evolved as an effective solution for client and business application advancement. It deals with large number of different types of resources. So in order to deliver these cloud facilities and services effectively, testing of the cloud based services turns out to be an essential step before its usage by the clients. For testing cloud applications there are various tools and methods. In this paper we analyze the use of various performance testing tools used in cloud environment and the correlation of the same for testing of cloud applications. Also we had gathered the expert reviews about the tools with the assistance of a review on survey monkey website over a time of one week. A sum of 20 working professionals had demonstrated enthusiasm for our overview that incorporates cloud professionals working in different Information Technology sector. The outcomes depict the tools which are most widely used by the cloud professionals.